2015
DOI: 10.1001/jama.2015.8369
|View full text |Cite|
|
Sign up to set email alerts
|

Brief Motivational Intervention for Intimate Partner Violence and Heavy Drinking in the Emergency Department

Abstract: Intimate partner violence (IPV) and heavy drinking are co-occurring public health problems, but integrated brief interventions for these conditions have not been tested.OBJECTIVE To determine whether a brief motivational intervention provided at the time of an emergency department (ED) visit reduces IPV and heavy drinking. DESIGN, SETTING, AND PARTICIPANTSA randomized clinical trial conducted at 2 US academic urban EDs between January 2011 and December 2014 to assess the effectiveness of a motivational interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 34 publications
1
66
0
1
Order By: Relevance
“…Two studies targeted stress and one reproductive health. The combination of outcomes assessed were violence and mental health in six studies (Coker et al, 2012; El-Mohandes et al, 2008; Fallot et al, 2012; Johnson et al, 2011; Joseph et al, 2009; Zlotnick, Capezza, & Parker, 2011), violence, mental health, and HIV risk in one study (Gilbert et al, 2006), mental health and HIV risk in four studies (Cocozza et al, 2005; Ghee et al, 2009; Rountree et al, 2014; Zhang et al, 2013), violence and HIV risk in two studies (Mittal et al, 2017; Rhodes et al, 2015), stress and mental health in two studies (Dutton et al, 2013; Nicolaidis et al, 2012), and violence and reproductive health in one study (Kiely, El-Mohandes, El-Khorazaty, & Gantz, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies targeted stress and one reproductive health. The combination of outcomes assessed were violence and mental health in six studies (Coker et al, 2012; El-Mohandes et al, 2008; Fallot et al, 2012; Johnson et al, 2011; Joseph et al, 2009; Zlotnick, Capezza, & Parker, 2011), violence, mental health, and HIV risk in one study (Gilbert et al, 2006), mental health and HIV risk in four studies (Cocozza et al, 2005; Ghee et al, 2009; Rountree et al, 2014; Zhang et al, 2013), violence and HIV risk in two studies (Mittal et al, 2017; Rhodes et al, 2015), stress and mental health in two studies (Dutton et al, 2013; Nicolaidis et al, 2012), and violence and reproductive health in one study (Kiely, El-Mohandes, El-Khorazaty, & Gantz, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…With the exception of TREM (Fallot et al, 2011), all studies assessing future safety focused on IPV. The eligibility criteria for including women in the intervention trial was only IPV (Coker et al, 2012), both IPV and drug/alcohol use (Gilbert et al, 2006; Rhodes et al, 2015), IPV and sexual risk behavior (Mittal et al, 2017), IPV and PTSD (Johnson et al, 2011), or IPV as one of the risks (i.e., active smoking, depression, environmental tobacco exposure; El-Mohandes et al, 2008; Joseph et al, 2009; Kiely et al, 2010). TREM (Fallot et al, 2014) participants had a history of physical and/or sexual abuse and a co-occurring mental health and substance abuse problem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cunningham and colleagues, who conducted a brief intervention similar to Real Talk in that it was for primarily Black and Hispanic adolescents living in poverty in an urban area and took place in an emergency department, found that their intervention reduced self-reported moderate and severe dating violence victimization for up to one year following the intervention, even if it didn’t impact perpetration (Cunningham et al, 2013). Cunningham et al’s results are particularly notable given that a large-scale RCT conducted by a research team in Philadelphia recently concluded that there was no effect of a similar brief intervention for adult, alcohol-using, female victims of partner abuse in an emergency department setting (Rhodes et al, 2015). In short, the literature about the impact of brief intervention on either adult or adolescent partner abuse perpetration or victimization is too sparse, too disparate in terms of inclusion criteria, measures, and methods, and too divergent in results to be able to draw any conclusion about the potential for this form of tertiary prevention to be worthy of investment.…”
Section: Discussionmentioning
confidence: 99%
“…The sample of 32 adult women for our study was derived from a randomized control trial that took place in two urban academic emergency rooms/trauma centers (Rhodes et al 2015; Rhodes, Rodgers, Sommers, Hanlon & Crits-Christoph, 2014). The parent study sought to assess effectiveness of a manualized motivational interviewing (MI) intervention for IPV-involved women reporting problem drinking patterns at the time of their ED visit.…”
Section: Methodsmentioning
confidence: 99%